Coping Strategies Adopted by Patients Sustaining Major Burns - Butt, Muhammad Wajih Uddin; Hameed, Shahid; Tahir, Manya; Nasir, Muhammad Ali; Mehmood, Farman; Alam, Khurshid (Pakistan Armed Forces Medical Journal, 2023)
Objective: To explore the various coping strategies used by patients sustaining major burns. Study Design: Qualitative, exploratory study. Place and Duration of Study: Department of Plastic and Reconstructive Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Jan to Jun 2021. Methodology: A total of 15 patients were selected who had been admitted to CMH Rawalpindi after sustaining 20-45% total body surface area deep dermal or full thickness burns requiring operative intervention. Semi-structured interviews comprising eleven questions were conducted, and the strategies which these patients used to cope with different psychological issues post-major burns were identified. Subthemes and themes were identified, and the data was analyzed by manual thematic analysis. Results: Eight coping strategies were identified: help from religion, support from family and friends, use of recreational activities, getting out of the house, doing exercise, getting back into a routine, the role of doctors and the use of the internet. Conclusion: Solace from religion and support from family and friends were the most widely used coping strategies in our setup. Getting back to routine helped them feel normal. Relaxation techniques and exercise were helpful but infrequently used. Social media and the internet were used as a diversion and recreational tool. None of our patients went for psychological counselling or group therapy sessions or used anxiolytics or antidepressants, which are an important part of treatment in the West.